Global Wave Hindcasts Using the Observation‐Based Source Terms: Description and Validation. (18th August 2021) - Liu, Qingxiang; Babanin, Alexander V.; Rogers, W. Erick; Zieger, Stefan; Young, Ian R.; Bidlot, Jean‐Raymond; Durrant, Tom; Ewans, Kevin; Guan, Changlong; Kirezci, Cagil; Lemos, Gil; MacHutchon, Keith; et al.
Abstract: Global wave hindcasts are developed using the third generation spectral wave model WAVEWATCH III with the observation‐based source terms (ST6) and a hybrid rectilinear‐curvilinear, irregular‐regular‐irregular grid system (approximately at 0.25 ° × 0.25 ° ). Three distinct global hindcasts are produced: (a) a long‐term hindcast (1979–2019) forced by the ERA5 conventional winds U 10 and (b) two short‐term hindcasts (2011–2019) driven by the NCEP climate forecast system (CFS)v2 U 10 and the ERA5 neutral winds U 10, n e u, respectively. The input field for ice is sourced from the Ocean and Sea Ice Satellite Application Facility (OSI SAF) sea‐ice concentration climate data records. These wave simulations, together with the driving wind forcing, are validated against extensive in‐situ observations and satellite altimeter records. The performance of the ST6 wave hindcasts shows promising results across multiple wave parameters, including the conventional wave characteristics (e.g., wave height H s and wave period) and high‐order spectral moments (e.g., the surface Stokes drift and mean square slope). The ERA5‐based simulations generally present lower random errors, but the CFS‐based run represents extreme sea states (e.g., H s > 10  m) considerably better. Novel wave parameters available in our hindcasts, namely the dominant wave breaking probability, wave‐induced mixed layer depth, freak wave indexes and wave‐spreading factor, are further described and briefly discussed. Inter‐comparisons of H s from the long‐term (41 years) wave hindcast, buoy measurements and two different calibrated altimeter data sets highlight the inconsistency in these altimeter records arising from different calibration methodology. Significant errors in the low‐frequency bins (period T > 15  s) for both wave energy and directionality call for further model development. Plain Language Summary: Ocean surface waves are fundamentally important for ocean engineering design, ship navigation, air‐sea exchange of gas, heat, momentum and energy, upper ocean dynamics, and remote sensing of the ocean. Spectral wave modeling is an indispensable tool to estimate sea state information. In this study, we present new global wave hindcasts developed using the state‐of‐the‐art model physics and numerics and the modern reanalysis winds and satellite sea ice records. It is demonstrated through validation against in‐situ observations and altimeter records that the global wave hindcasts perform well across multiple parameters. Meanwhile, intercomparisons of wave height from the long‐term hindcast, buoys, and altimeters reveal inconsistency and potential inhomogeneity in these different data sets. The wave hindcasts we developed, in combination with global wave databases published previously, will form a large ensemble of realizations of historical evolution of sea states simulated with distinct wave physics and wind forcing, which will help quantify sea states in real oceans more accurately. Key Points: Global wave hindcasts using the observation‐based source terms are developed and validated against extensive observations The wave hindcasts show promising performance across multiple parameters, including wave height, period, and high‐order spectral moments Intercomparisons of wave height from the hindcast, buoys, and altimeters highlight the inconsistency and inhomogeneity in these data sets